2002
DOI: 10.1136/jech.56.4.246
|View full text |Cite
|
Sign up to set email alerts
|

Can lay-led walking programmes increase physical activity in middle aged adults? A randomised controlled trial

Abstract: Study objective: To compare health walks, a community based lay-led walking scheme versus advice only on physical activity and cardiovascular health status in middle aged adults. Design: Randomised controlled trial with one year follow up. Physical activity was measured by questionnaire. Other measures included attitudes to exercise, body mass index, cholesterol, aerobic capacity, and blood pressure. Setting: Primary care and community. Participants: 260 men and women aged 40-70 years, taking less than 120 min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
104
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(108 citation statements)
references
References 17 publications
3
104
0
Order By: Relevance
“…They included five studies with measures of physical activity and reported significant effects for three of these studies. However, in two of the studies [30,31], the interventions were delivered by laypersons, not peers. Of the remaining three studies, none included an intervention specifically designed to increase physical activity-one intervention was designed to increase self-efficacy after myocardial infarction [32] and the other two were disease self-management programs [33,34].…”
Section: Peer Mentors and Health Intervention Deliverymentioning
confidence: 99%
“…They included five studies with measures of physical activity and reported significant effects for three of these studies. However, in two of the studies [30,31], the interventions were delivered by laypersons, not peers. Of the remaining three studies, none included an intervention specifically designed to increase physical activity-one intervention was designed to increase self-efficacy after myocardial infarction [32] and the other two were disease self-management programs [33,34].…”
Section: Peer Mentors and Health Intervention Deliverymentioning
confidence: 99%
“…20,23 The duration of the schemes was 10 or 12 weeks in four RCTs, [18][19][20]23 4 months in one non-randomised study, 24 and up to 2 years in one RCT. 21 There appeared to be no time limit (or none mentioned) for the walking scheme reported by Lamb et al 22 The participants of most schemes were adults (mainly middle-aged) with sedentary lifestyles and cardiac risk factors, and the aims were to increase physical activity and reduce cardiac risk factors. The quality of these studies varied from 15 to 29 (median 26) out of a maximum of 34 on the quality score (Supplementary Table 3); 12 none of the RCTs scored less than 19.…”
Section: Controlled Studies Including Rctsmentioning
confidence: 99%
“…23 The unit of randomisation was the individual participant in five trials, [18][19][20]22,23 and the referring practice in one trial. 21 A non-randomised controlled study compared a walking programme for patients with type 2 diabetes with no programme.…”
Section: Controlled Studies Including Rctsmentioning
confidence: 99%
See 2 more Smart Citations